"Managing the Impossible?" Comparing How Countries Address the Dahrendorf Quandary. Issue 6 (2nd November 2022) - Anheier, Helmut K.; Filip, Alexandru
Abstract: This paper examines the policy approaches and measures that developed market economies countries have adopted to "manage" what has become known as the Dahrendorf Quandary, a profound challenge facing globalizing economies: over time, staying economically competitive requires either adopting measures detrimental to the cohesion of society or restricting civil liberties and political participation. Examining a range of countries over time, it is found that their policy choices and subsequent performance are too varied to support the inevitable, almost mechanical, incompatibility the Quandary implies. While balancing the relationship between economic globalization, social cohesion, and democracy continues to be a major challenge for developed market economies, results show they are not helpless in what Dahrendorf feared to be a Herculean task of "squaring the circle" among incompatible trends. In other words, while the tensions the Quandary posits apply, they nonetheless need not lead to similar or negative outcomes.